HOW CORPORATE GOVERNANCE AND FINANCIAL POLICY SHAPE FIRM VALUE - Safitri Purwanti Ningsih, Helis; Savitri, Enni; Wiguna, Meilda (Universitas Riau, 2026)
This study aims to examine the dynamics of firm value creation by integrating Agency Theory, Signalling Theory, and Trade-off Theory. Despite the extensive literature on corporate governance and financial policy, inconsistent empirical findings in emerging markets post-pandemic have created a research gap that warrants further exploration. Using a purposive sampling method, this study analyzes 76 manufacturing companies listed on the Indonesia Stock Exchange for the period 2021–2023, resulting in 228 panel data observations processed using STATA 17. The analysis reveals that governance structures (Board of Directors and Commissioners) and capital structure play a crucial role in reducing agency costs and providing positive signals that enhance firm value. Conversely, the Audit Committee is found to have a negative influence, suggesting oversight redundancy or symbolic compliance. Anomalies are observed in dividend policy and audit quality, which are insignificant, indicating a shift in investor preferences in volatile markets. This research contributes internationally by providing empirical evidence on how internal control mechanisms and financial decisions interact to restore market confidence in emerging markets.